An Investigation on the Park and People Problems: Special Emphasis on the Impact on Wetland Surrounding Vegetation due to Overgrazing of Livestock in Koshi Tappu Wildlife Reserve, Nepal : (A Case Study of Kusaha VDC) - Shrestha, Anu; Chhetri, Rana Bahadur; Khanal, Sanjay Nath (Kathmandu University Journal of Science, Engineering and Technology, 2006)
Koshi Tappu Wildlife Reserve (KTWR) is an important wetland area in the floodplain of Sapta Koshi River in the east terai of Nepal. It covers about 150 km2 area. It is decorated by a total of 515 species of plants consisting submerged, floating species as well as grassland/subannah and riverine forest.The study was carried out to investigate the impact of overgrazing by livestock on the wetlands surrounding vegetation characteristics of KTWR. Surrounding areas of two wetlands, one from inside the reserve named as ‘Station Wetland’ (SW site) and other, in the buffer zone, outside the reserve named as ‘Khanta Wetland’ (KW site) were selected for the study. Station wetland was considered as the reference site where there was minimum grazing, whereas, the Khanta wetland was an overgrazed site. Vegetation study was done using 50 x 50 cm quadrate. In each site, 10 quadrates were thrown randomly. Species density and abundance of the vegetation were compared from both the sites.23 species of vegetation are recorded at KW site whereas 17 species were recorded SW site. Species density of KW site was 10.7 and that of SW site was 17.5. Common floras were Stellaria sp, Cyperus sp, Lantana sp, Sagina sp, Eurya sp, Erianthus ravenna, Sambucus sp, Cynoden sp, Vertiveria lawsonii, and Polygonum sp. Cyperus sp and Phragmites karka were having the highest density whereas Phragmites karka, Carex sp, Sambucus sp were most abundant in KW site. In SW site Vertiveria lawsonii, Cyperus sp, and Stellaria sp were having higher densities and Rumex nepalensis sp, Lencus sp, Lantana sp. were most abundant species. The relative abundance and density were higher inside the reserve compared to outside. The vegetations found inside the reserve were relatively taller too.It has been found that grazing is one of the major threats to the wetlands in Koshi Tappu and is a major issue generating conflicts between local people and management of the reserve. In a typical day almost 1000 livestock were recorded grazing around the wetland outside the reserve.